In Vitro Antibacterial and Antioxidant Activities, Pharmacokinetics, and In Silico Molecular Docking Study of Phytochemicals from the Roots of Ziziphus spina-christi - Hadush Gebrehiwot; Urgessa Ensermu; Aman Dekebo; Milkyas Endale; Tariku Nefo Duke (Biochemistry Research International)
Ziziphus spina-christi (Rhamnaceae family) is a medicinal plant traditionally used to treat dandruff, wounds, hair loss, diarrhea, mastitis, abdominal pain, and gastrointestinal complications. To support this, the present work aims to study the in vitro antibacterial and antioxidant activities of compound isolates from the roots of Ziziphus spina-christi along with their in silico computational analyses. Compounds were isolated on silica gel column chromatography and an agar disc diffusion and DPPH radical scavenging assays were employed to study the antibacterial and antioxidant activities, respectively. The ADME and toxicity properties of the compounds were evaluated using SwissADME and ProTox-II online Web tools, respectively. Conversely, the in silico molecular docking studies were attained via a Biovia Discovery Studio Visualizer 2021 in combination with the AutoDock Vina software. The silica gel chromatographic separation of the combined CH2Cl2 : CH3OH (1 : 1) and CH3OH root extracts afforded trimethyl trilinolein (1), stearic acid (2), 13-hydroxyoctadeca-9, 11-dienoic acid (3), β-sitosteryl-3β-glucopyranoside-6′-O-palmitate (4), and stigmasterol (5). Notably, the in vitro antibacterial study revealed the extract and β-sitosteryl-3β-glucopyranoside-6′-O-palmitate (4) with the highest inhibitory activities (15.25 ± 0.35 and 14.25 ± 0.35 mm, respectively) against E. coli compared to ciprofloxacin (21.00 ± 0.35 mm) at 2 mg/mL. The CH2Cl2 : CH3OH (1 : 1) extract (IC50 : 1.51 µg/mL) and β-sitosteryl-3β-glucopyranoside-6′-O-palmitate (4) (IC50 : 5.41 µg/mL) also exhibited auspicious DPPH scavenging activities, followed by stigmasterol (5) (IC50 : 6.88 µg/mL) compared to the ascorbic acid standard (IC50 : 0.46 µg/mL). The molecular docking analyses unveiled the highest binding affinity by β-sitosteryl-3β-glucopyranoside-6′-O-palmitate (4) (−8.0 kcal/mol) against P. aeruginosa PqsA relative to the ciprofloxacin standard (−8.2 kcal/mol). Furthermore, the organ toxicity predictions showed that all the compounds exhibit no hepatotoxicity and cytotoxicity effects and stigmasterol (5) affords drug-likeness protocols. Overall, the combined experimental and computational investigations of this study support the traditional uses of Ziziphus spina-christi for antibacterial and natural antioxidant applications.